Design Of Website-Based Height Waves Information System - Muhamad Rakif Panguale; Indra Jaya; Totok Hestirianoto (Journal of Applied Geospatial Information, 2019)
One of the environmental parameters that need to be monitored is ocean waves. Waves that occur at sea have random, dynamic, and complex movements. Height measurements and wave periods are difficult to formulate accurate and simplification is needed through mathematical equations in the form of sinusoidal. Therefore, the marine information system is very important for data storage media, data processing, and visualization of measurement data so that it is monitored in real-time. This research was made to build a website-based coastal wave height monitoring information system for wave height data display data from the measurement of the wave buoy instrument. This research was conducted by utilizing data from a wave height measuring instrument that was transmitted to an online database. Wave height data is displayed in the form of real-time data, real-time graphs with data sampling of 30 minutes, average data for one day, and average data for one month. Keywords: Wave height, system information, real-time